Very small embryonic-like stem cells have the potential to win the three-front war on tissue damage, cancer, and aging - Bhartiya, Deepa; Jha, Nitu; Tripathi, Anish; Tripathi, Ashish (Frontiers in Cell and Developmental Biology, 2023)
The concept of de-differentiation and reprogramming of mature somatic cells back to pluripotent state is being applied on multiple fronts. It was hoped that reprogrammed human somatic cells into induced pluripotent (iPS) along with embryonic stem cells would transform regenerative medicine. But despite global efforts, clinical applications remain a distant dream due to associated concerns like genomic instability, tumorigenicity, immunogenicity and heterogeneity. Expression of embryonic (pluripotent) markers in multiple cancers has baffled scientific community and it is suggested that somatic, fully differentiated cells dedifferentiate and ‘reprogram’ in vivo to pluripotent state to initiate cancer. Thirdly, it is being suggested that aging can be reversed by partial reprogramming in vivo. But better methods need to evolve since putting vectors/ Yamanaka factors in vivo is dangerous and may face similar concerns as for iPS cells. Present perspective posits that war on all these three fronts can be won by acknowledging presence of endogenous, pluripotent very small embryonic-like stem cells (VSELs) in multiple tissues that routinely replace diseased tissues and ensure regeneration to maintain life-long homeostasis. VSELs have the ability to differentiate into adult counterparts and recent evidence suggests that cancers initiate due to selective expansion of epigenetically altered VSELs and their blocked differentiation. Also, VSELs numbers have been linked to lifespan by studies on long and short-lived transgenic mice and VSELs dysfunction was reported in aged mice ovaries. To conclude, light at the end of tunnel to win the war on all three fronts will come by acknowledging VSELs and their potential.